Menstrual cycle and thermoregulation during exercise in the heat: A systematic review and meta-analysis. Issue 12 (December 2020) - Giersch, Gabrielle E.W.; Morrissey, Margaret C.; Katch, Rachel K.; Colburn, Abigail T.; Sims, Stacy T.; Stachenfeld, Nina S.; Casa, Douglas J.
Abstract: Research conducted on exercise in the heat has been largely conducted in males, leaving women understudied. Of research including women, results are inconsistent on the impact of menstrual cycle phase on thermoregulation. Objectives: The purpose of this systematic review is to quantify published investigations in thermal physiology that include menstrual cycle comparisons and assess aggregate data of investigations that include menstrual cycle variation and aerobic exercise in the heat. Methods: 367 research articles were identified via systematic review and inclusion criteria and yielded 9 papers included in this analysis for a total number of 83 research subjects. Effect size estimates (Hedge's g ) were utilized for initial (pre-exercise) and post-exercise internal body temperature (rectal or esophageal, T int ), sweat rate, mean skin temperature, and exercise heart rate. Results: Pooled effect size showed significantly greater initial T int (1.231 ± 0.186, p  < 0.01) and post-exercise T int (0.455 ± 0.153, p  < 0.01) in the luteal compared to follicular phases. No significant differences were present in mean skin temperature, sweat rate, or exercise heart rate across menstrual phases in analyses of aggregate data. Conclusions: The limited available data suggest that observed increases in initial T int in the luteal phase are maintained throughout and post-exercise without an observed impact in sweat rate or mean skin temperature.